Penguatan Hukum Adat Sebagai Upaya Perlindungan Lingkungan Hidup Berbasis Kearifan Lokal - Yuli Petiwi Ningsih; Gunawan Hadi Purwanto (Darma Cendika Catholic University, 2026)
Abstract Customary law (adat law) constitutes a living legal system that has evolved within Indonesian society and embodies the values of local wisdom. In the context of environmental protection, customary law plays a significant role in regulating the sustainable use of natural resources through customary norms, values, and sanctions observed by indigenous communities. Although constitutionally recognized, the implementation of customary law within Indonesia's national legal system continues to encounter various challenges, including regulatory inconsistencies, limited legal recognition of indigenous peoples, and the inadequate integration of local wisdom into environmental governance. This study aims to analyze the status and legal position of customary law within Indonesia's national legal system and to examine strategies for strengthening customary law in supporting environmental protection based on local wisdom. The research employs a normative legal method using statutory, conceptual, and case approaches, supported by library research and qualitative legal analysis. The findings indicate that strengthening customary law requires regulatory harmonization, stronger legal recognition and protection of indigenous peoples and their customary territories, institutional reinforcement of customary governance, and the incorporation of local wisdom into environmental protection and management policies. These measures are expected to strengthen Indonesia's national legal system while promoting sustainable development and ecological justice.